Micromotives and macrobehavior - Schelling, Thomas C. (New York Norton, 2006)
Micromotives and Macrobehavior was originally published over twenty-five years ago, yet the stories it tells feel just as fresh today. And the subject of these stories―how small and seemingly meaningless decisions and actions by individuals often lead to significant unintended consequences for a large group―is more important than ever. In one famous example, Thomas C. Schelling shows that a slight-but-not-malicious preference to have neighbors of the same race eventually leads to completely segregated populations.
New edition"--P. 3.
Keywords: Policy sciences